the Change in Retentive Values of O-Ring and Magnetic attachments in Mandibular implant supported overdentures over periods of time (an In Vitro Study) - Omar Samy Mahmoud (2012)
Arabic Summary .
MD in Prosthodontics
Cairo University, Faculty Of Oral and Dental Medicine .
Keywords: Mandibular